2009
DOI: 10.1179/174313209x385707
|View full text |Cite
|
Sign up to set email alerts
|

Stronger expression of CHOP and caspase 12 in diabetic spinal cord injury rats

Abstract: These results suggest that stronger ER stress in diabetic rats may be the reason for severe SCI observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
12
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 30 publications
2
12
0
Order By: Relevance
“…ER stress-induced cell death has been shown to involve the activation of caspase-12, which subsequently activates executer caspases such as caspase-3 [20, 21, 48, 49]. Caspase-12 is specific to insults that elicit ER stress and is not proteolytically activated by other death stimuli [20].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ER stress-induced cell death has been shown to involve the activation of caspase-12, which subsequently activates executer caspases such as caspase-3 [20, 21, 48, 49]. Caspase-12 is specific to insults that elicit ER stress and is not proteolytically activated by other death stimuli [20].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, RQKL also decreased caspase-3 level significantly. Caspase-3 activation is involved in caspase-12 mediated apoptotic cascade, while activated caspase-3 is directly responsible for DNA fragmentation [20, 21, 48]. It is possible that caspase-3 activation is inhibited by suppression of caspase-12.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, activation of the unfolded protein response (UPR) upregulates the expression and activity of caspase-12 and may be important in neuronal cell death in ischemic brain injury (9). It has also been observed that the activation of caspase-12 is involved in the apoptosis of spinal cord neurons and oligodendrocytes, which is induced by oxygen-glucose-serum deprivation/restoration (10,11). Therefore, the inhibition of caspase-12 expression following SCI may potentially be used as a therapeutic target for neuron protection.…”
Section: Introductionmentioning
confidence: 99%
“…8) As a pre-apoptotic factor, CHOP is suggested to activate caspase cascade by inducing cleavage of caspase-12 (rodents) 9) or caspase-4 (human). 10) In recent decades, natural products gradually become new alternatives besides regular therapies. With a long history in traditional medicine in East Asia, ginseng (Panax quinquefolius) is now a very popular herb as medicine or food supplement in the world.…”
mentioning
confidence: 99%